Important Contributions of the South American Record to the Understanding of Dinosaur Reproduction - Fernández, Mariela (2016)
South American fossil eggs display a very rich record in the Cretaceous, which permits an understanding of dinosaur reproduction. In this paper I review all dinosaur ootaxa described at the moment and discuss their relationships and geographical distribution. Macro characters of eggshells were studied and interpreted as a possible source of paleobiological knowledge, whereas several other macro characters are questioned or discussed. Three megaloolithid oospecies have been described for North Patagonia, and they have been compared with worldwide materials revealing the Gondwana distribution. Two fusioolithid eggshells were described, and one of them, Fusioolithis baghensis, was synonymized with Indian, French and Spanish materials, indicating that this widespread oospecies was laid by titanosaurs because they share the same features as the Auca Mahuevo eggs. Faveoloolithid eggs have been compared from La Rioja, La Pampa, Uruguay and Patagonia, reflecting that one kind of dinosaur was reproducing in all Argentina and Uruguay with this kind of eggshell. Theropod eggs have been described from Río Negro province, and ornithothoracean eggs have been compared from Neuquén city with those of Brazil, and apparently the same group was reproducing in both areas during the Late Cretaceous.